Impact of stress on male fertility: role of gonadotropin inhibitory hormone - Odetayo, Adeyemi F.; Akhigbe, Roland E.; Bassey, Grace E.; Hamed, Moses A.; Olayaki, Luqman A. (Frontiers in Endocrinology, 2024)
Studies have implicated oxidative stress-sensitive signaling in the pathogenesis of stress-induced male infertility. However, apart from oxidative stress, gonadotropin inhibitory hormone (GnIH) plays a major role. The present study provides a detailed review of the role of GnIH in stressinduced male infertility. Available evidence-based data revealed that GnIH enhances the release of corticosteroids by activating the hypothalamic-pituitary-adrenal axis. GnIH also mediates the inhibition of the conversion of thyroxine (T4) to triiodothyronine (T3) by suppressing the hypothalamic-pituitary-thyroidal axis. In addition, GnIH inhibits gonadotropin-releasing hormone (GnRH), thus suppressing the hypothalamic-pituitary-testicular axis, and by extension testosterone biosynthesis. More so, GnIH inhibits kisspeptin release. These events distort testicular histoarchitecture, impair testicular and adrenal steroidogenesis, lower spermatogenesis, and deteriorate sperm quality and function. In conclusion, GnIH, via multiple mechanisms, plays a key role in stress-induced male infertility. Suppression of GnIH under stressful conditions may thus be a beneficial prophylactic and/or therapeutic strategy.